The Influence of Learning Media Utilization, Critical Thinking Skills, and Student Motivation on Learning Effectiveness - Andriani Sariwardani; Eka Noviani Lestari; Wiwi Widya Lestari; Komalawati (Journal Management & Economics Review (JUMPER), 2026)
This study aims to examine the influence of learning media utilization, critical thinking skills, and student motivation on learning effectiveness. Using a quantitative explanatory research design, data were collected from 200 students through structured questionnaires measured on a five-point Likert scale. The data were analyzed using multiple linear regression analysis to determine both partial and simultaneous effects among variables. The results reveal that learning media utilization has a positive and significant effect on learning effectiveness, indicating that well-integrated instructional media enhance students’ understanding and engagement. Critical thinking skills also show a positive and significant influence, suggesting that students with stronger analytical and evaluative abilities achieve more effective learning outcomes. Furthermore, student motivation emerges as the most dominant variable affecting learning effectiveness, demonstrating that motivated students are more persistent, engaged, and successful in achieving learning objectives. Simultaneously, the three independent variables significantly influence learning effectiveness, explaining 52.3% of its variance. These findings highlight the importance of integrating innovative learning media, fostering higher-order thinking skills, and strengthening student motivation to achieve optimal educational outcomes. The study provides practical implications for educators and institutions in designing holistic and student-centered instructional strategies to enhance learning effectiveness.